APPLICATION OF IQRA’ METHOD IN STRENGTHENING THE QUALITY OF QUR’AN RECITATION: A CASE STUDY OF STUDENTS OF MADRASAH TSANAWIYAH QORYATUL QUR’AN WERU SUKOHARJO - Sulistyan, Daffa Luqman; Muslimin, Edy; Nurhidayati, Indah (STKIP Pesisir Selatan, 2025)
Objective: This study aims to analyze the application of the Iqra Method in strengthening the quality of Qur'an recitation of MTs Qoryatul Qur'an Weru Sukoharjo students. The main focus of the research is to assess the effectiveness of this method in improving the accuracy of machraj, the application of tajweed laws, and the fluency of students' recitation. The background of the study is based on the low quality of Qur'anic reading among madrasah students, so an approach that not only emphasizes basic literacy, but also fosters sustainable reading that is tartil and religious is needed. Methods: The research used a descriptive qualitative approach with a case study design. The research subjects consisted of one tahfiz teacher and ten seventh grade students selected by purposive sampling. Data were obtained through observation, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman interactive model through the stages of data reduction, presentation, and verification. Validity was strengthened by triangulation of sources and techniques. Results: The results showed that the gradual, systematic, and corrective application of the Iqra Method improved students' ability to pronounce letters, apply the laws of tajweed, and read fluently and correctly.